The Dominant Folding Route Minimizes Backbone Distortion in SH3 - Lammert, Heiko; Noel, Jeffrey K.; Onuchic, José N. (PLOS Computational Biology, 2012)
Author Summary Proteins are involved in all aspects of life. To perform their biological function, each protein chain has to fold into a unique three-dimensional structure. This conformational search can only succeed because all interactions are optimized by evolution to create a smooth funnel-shaped energy landscape with a consistent native bias. With the energetics thus leveled, geometrical constraints come to dominate the folding mechanism. But the same interactions that shape the folding mechanism also shape the functional dynamics of the folded protein. Specific functional requirements can thus introduce frustrated interactions that will show up in turn as anomalies in the folding process. In order to extract this functional information a quantitative understanding of the minimally frustrated folding landscape is required. We have devised a method to quantify the contributions from entropy and energy terms that determine the folding mechanism in a model with a perfectly funneled energy landscape. We find for an SH3 domain that its folding mechanism is determined by the energy cost for distortions of the backbone, a term that is usually disregarded in qualitative discussions of protein folding. In general, by counterbalancing the expected dominance of the configurational entropy, the backbone potential should facilitate functional adjustments of the folding mechanism.